MacEwan University Library's experiences with Pressbooks - Hall, Robyn (My University, 2022)
Brief presentation detailing MacEwan University Library's initial experiences using Pressbooks software to support the MacEwan Open Books open textbook hosting service.
Presented on March 2, 2022 at the NEOS OER Workshop held online.
Keywords: open education resources; Pressbooks; open textbooks; open source software